Answer: A reelection across the Y axis, then a reflection across the X axis.
Step-by-step explanation:
Answer:
![(x,y) = (0,4)~ \text{and}~ (x,y) = (2,8)](https://tex.z-dn.net/?f=%28x%2Cy%29%20%3D%20%280%2C4%29~%20%5Ctext%7Band%7D~%20%28x%2Cy%29%20%3D%20%282%2C8%29)
Step by step explanation:
![y = x^2 +4~~~~~~~~~...(i)\\\\y = 2x +4~~~~~~~~~...(ii)\\\\\text{From (i) and (ii):}\\\\~~~~~~x^2 +4 = 2x+4\\\\\implies x^2 = 2x\\\\\implies x^2 -2x = 0\\\\\implies x(x-2) = 0\\\\\implies x =0,~ x = 2](https://tex.z-dn.net/?f=y%20%3D%20x%5E2%20%2B4~~~~~~~~~...%28i%29%5C%5C%5C%5Cy%20%3D%202x%20%2B4~~~~~~~~~...%28ii%29%5C%5C%5C%5C%5Ctext%7BFrom%20%28i%29%20and%20%28ii%29%3A%7D%5C%5C%5C%5C~~~~~~x%5E2%20%2B4%20%3D%202x%2B4%5C%5C%5C%5C%5Cimplies%20x%5E2%20%3D%202x%5C%5C%5C%5C%5Cimplies%20x%5E2%20-2x%20%3D%200%5C%5C%5C%5C%5Cimplies%20x%28x-2%29%20%3D%200%5C%5C%5C%5C%5Cimplies%20x%20%3D0%2C~%20x%20%3D%202)
![\text{Substitute x = 0 in eq (i):}\\\\y = 0^2 +4 = 4\\\\\text{Substitute x = 2 in eq (i):}\\\\y=2^2+4 = 4+4 = 8\\\\\text{Hence,}~ (x,y)= \{(2,8), (0,4)\}](https://tex.z-dn.net/?f=%5Ctext%7BSubstitute%20x%20%3D%200%20in%20eq%20%28i%29%3A%7D%5C%5C%5C%5Cy%20%3D%200%5E2%20%2B4%20%3D%204%5C%5C%5C%5C%5Ctext%7BSubstitute%20x%20%3D%202%20in%20eq%20%28i%29%3A%7D%5C%5C%5C%5Cy%3D2%5E2%2B4%20%3D%204%2B4%20%3D%208%5C%5C%5C%5C%5Ctext%7BHence%2C%7D~%20%28x%2Cy%29%3D%20%5C%7B%282%2C8%29%2C%20%280%2C4%29%5C%7D)
Answer:13746
Step-by-step explanation:
3 * 79 = find amount of pages on average per book
= 237
237 * 58 = find amount of pages written for 58 books
=13746
James Patterson has written approximately 13,746 pages
Answer:
The equation of the line is y = 1/4x - 4
Step-by-step explanation:
In order to find this, start with two points that are on the line. We'll use (0, -4) and (4, -3). Now we can use the slope formula to find the slope.
m(slope) = (y2 - y1)/(x2 - x1)
m = (-4 - -3)/(0 - 4)
m = -1/-4
m = 1/4
Now that we have this, we can use that slope and a point in point-slope form. Then we solve for y to get the equation.
y - y1 = m(x - x1)
y - -4 = 1/4(x - 0)
y + 4 = 1/4x
y = 1/4x - 4